Probing of the interfacial Heisenberg and Dzyaloshinskii–Moriya exchange interaction by magnon spectroscopy. (10th November 2016) - Zakeri, Khalil
Abstract: This Topical Review presents an overview of the recent experimental results on the quantitative determination of the magnetic exchange parameters in ultrathin magnetic films and multilayers grown on different substrates. The experimental approaches for probing both the symmetric Heisenberg and the antisymmetric Dzyaloshinskii–Moriya exchange interaction in ultrathin magnetic films and at interfaces are discussed in detail. It is explained how the experimental spectrum of magnetic excitations can be used to quantify the strength of these interactions.